#TITLE_ALTERNATIVE# - RETNOWULAN (NIM 10104015), HASTUTI
This final project contains the study about decoding of cyclic code using error-correcting pair from the class of MDS (Maximum Distance Separable) code. The method studied can be implemented in an algorithm which finds a t-error-correcting-pair. The method can then correct the errors in the received word as long as the numbers of errors in not more than t. The method also enables us to maximize the capability of error-correcting-pair in correcting the number of errors.